Numerical and experimental study of natural convection heat transfer on flat and corrugated plates - Verdério Júnior, Sílvio Aparecido; Coelho, Pedro J.; Scalon, Vicente Luiz [UNESP]; del Rio Oliveira, Santiago [UNESP] (Emerald, 2023)
Purpose: The purpose of this study is to numerically and experimentally investigate the natural convection heat transfer in flat plates and plates with square, trapezoidal and triangular corrugations. Design/methodology/approach: This work is an extension of the previous studies by Verderio et al. (2021a, 2021b, 2021c, 2021d, 2022a). An experimental apparatus was built to measure the plates’ temperatures during the natural convection cooling process. Several physical parameters were evaluated through the experimental methodology. Free and open-source computational tools were used to simulate the experimental conditions and to quantitatively and qualitatively evaluate the thermal plume characteristics over the plates. Findings: The numerical results were experimentally validated with reasonable accuracy in the range of studied (Formula presented.) for the different plates. Empirical correlations of (Formula presented.), (Formula presented.) and (Formula presented.), with good accuracy and statistical representativeness, were obtained for the studied geometries. The convective thermal efficiency of corrugated plates (Δη), as a function of (Formula presented.), was also experimentally studied quantitatively. In agreement with the findings of Oosthuizen and Garrett (2001), the experimental and numerical results proved that the increase in the heat exchange area of the corrugations has a greater influence on the convective exchange and the thermal efficiency than the disturbances caused in the flow (which reduce (Formula presented.)). The plate with trapezoidal corrugations presented the highest convective thermal efficiency, followed by the plates with square and triangular corrugations. It was also proved that the thermal efficiency of corrugated plates increases with (Formula presented.). Practical implications: The results demonstrate that corrugated surfaces have greater thermal efficiency than flat plates in heating and/or cooling systems by natural convection. This way, corrugated plates can reduce the dependence on auxiliary forced convection systems, with application in technological areas and Industry 4.0. Originality/value: The empirical correlations obtained for the corrected Nusselt number and thermal efficiency for the corrugated plate geometries studied are original and unpublished, as well as the experimental validation of the developed three-dimensional numerical code.
Keywords: Corrugated plates; Empirical correlations; Natural convection; OpenFOAM®; Validation